DOI: 10.11606/d.11.2008.tde-15102008-080051
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de glicerol na dieta de suínos em crescimento e terminação

Abstract: Utilização de glicerol na dieta de suínos em crescimento e terminaçãoAo amigo José Aparecido Moreira, pela inestimável ajuda e sugestões;Aos novos e grandes amigos Amanda, Rogério, Fernando e Nina, pela amizade e momentos vividos;À minha querida Tatá, que dedicou vários anos da vida à mim e à minha família, diariamente, com muito carinho e atenção; À querida Malu, pela atenção e incentivo à mim e dedicação e amor ao meu pai durante todos esses anos; À todos que de maneira direta ou indireta contribuíram para a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
12
1
6

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 3 publications
9
12
1
6
Order By: Relevance
“…Resultados semelhantes aos deste estudo também foram encontrados por Berenchtein et al (2010) que, trabalhando com glicerina semipurificada (80g/100g de glicerol) como ingrediente energético das rações de suínos em crescimento e terminação até o nível de 90g/kg, não verificaram efeito (P<0,05) sobre os valores de pH, perda de peso por gotejamento e luminosidade. Lammers et al (2008), avaliando níveis de 0, 50 e 100g/kg de inclusão de glicerina na dieta, também não relataram influência da dieta sobre os parâmetros de qualidade de carne.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Resultados semelhantes aos deste estudo também foram encontrados por Berenchtein et al (2010) que, trabalhando com glicerina semipurificada (80g/100g de glicerol) como ingrediente energético das rações de suínos em crescimento e terminação até o nível de 90g/kg, não verificaram efeito (P<0,05) sobre os valores de pH, perda de peso por gotejamento e luminosidade. Lammers et al (2008), avaliando níveis de 0, 50 e 100g/kg de inclusão de glicerina na dieta, também não relataram influência da dieta sobre os parâmetros de qualidade de carne.…”
Section: Resultsunclassified
“…Mourot et al (1994), utilizando 5% de glicerina em dietas para suínos em terminação, verificaram uma maior capacidade de retenção de água no músculo Longissimus dorsi, proporcionando uma carne de qualidade superior. Berenchtein et al (2010), trabalhando com glicerina para suínos em terminação até o nível de 9%, não verificaram efeito sobre os valores de pH, perda de peso por gotejamento e luminosidade. Enquanto Gomide et al (2012) verificaram redução da perda de peso por descongelamento e da força de cisalhamento com aumento dos níveis de glicerina de até 16%, indicando melhora nos aspectos da qualidade da carne de suínos.…”
Section: Introductionunclassified
“…Biodiesel has the great advantage of being produced from renewable sources, such as oilseeds, mirrored by the enormous growth of its production and consequent supply of the byproduct glycerin, which was 69 m 3 in 2005 and rose to 3,419,838 m 3 in 2014 (ANP, 2015). The main component of glycerin, glycerol, is a highenergy compound present in feedstuffs and in the animal metabolism that has the potential to be used as a partial substitute for cereal grains or other high-starch ingredients in pig diets (Berenchtein et al, 2010;Gallego et al, 2014;Gomide et al, 2012); however, a consensus has not been reached as to its inclusion level in diets. Berenchtein et al (2010) reported that purified glycerin can be used at levels up to 9% in the diet, whereas Huepa et al (2015) asserted it is possible to include up to 12% without impairing the performance of finishing animals.…”
Section: Introductionmentioning
confidence: 99%
“…The use of glycerol in the formulation of diets stimulated immediate interest to obtain a rich in energy product (4320 kcal gross energy per kg of pure glycerol) and high efficiency of utilization by animals (Berenchtein et al 2010). Moreover, serving as an energy source, glycerol may also have a positive effect on nitrogen retention, improving the recovery of amino acids and reducing the emission of pollutants in the enviroment (Cerrate et al 2006, Berenchtein et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, serving as an energy source, glycerol may also have a positive effect on nitrogen retention, improving the recovery of amino acids and reducing the emission of pollutants in the enviroment (Cerrate et al 2006, Berenchtein et al 2010. Several studies involving pigs (Della Casa et al 2009, Seneviratne et al 2011, cattle b , Abo El-Nor et al 2010 and sheep (Terre et al 2011), have been developed to determine the effects of glycerol from different sources on performance, meat and milk quality and digestibility of nutrients.…”
Section: Introductionmentioning
confidence: 99%